Pengaruh Massage Counter Pressur Terhadap Pengurangan Nyeri Pada Persalinan Kala I Fase Aktif Di Klinik Vita Serasi Kabupaten Batu Bara Tahun 2022 - Nurhasanah Nurhasanah; Deby Cyntia Yun; Marliani Marliani; Imarina Tarigan (Jurnal Anestesi, 2023)
BACKGROUND: Childbirth is the process of expelling the viable products of conception in the uterus to the outside world. Normal labor and birth is the process of expulsion of the fetus that occurs at term pregnancy (37-42 weeks) spontaneous birth with a presentation of the back of the head which takes place within 18 hours, without complications for either the mother or fetus. In the first stage of labor, uterine contractions cause cervical dilation and push the fetus through the birth canal. Uterine contractions during labor cause pain, pain is caused by ischemia of the uterine muscles, pelvic floor muscles and perenium. The peak of pain occurs in the active phase where complete opening reaches 10 cm and lasts around 4-6 hours for primi para and 2-4 hours for multi para. Maternal health efforts are carried out in order to encourage every birth to be attended by trained health personnel, namely specialist obstetricians and gynecologists (SpOG), general practitioners and midwives, and are attempted to be carried out in health service facilities. Childbirth assistance is a delivery service process that starts from the first stage to the fourth stage of labor. Achievement of maternal health efforts during childbirth is measured through the indicator of the percentage of births assisted by trained health personnel (Pn Coverage). This indicator shows the level of the government's ability to provide quality delivery services assisted by trained health workers. OBJECTIVE: Knowing the Effect of Massage Counter Pressur on Reducing Pain in the First Stage of Active Phase Competition in Vita Serasi, Batu Bara Regency in 2022 METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. ADVICE There is an effect of massage counter pressure on reducing pain in competition during the first active phase in Vita Serasi Batu Bara Regency in 2022 SUGGESTION given for research and for research sites and for educational institutions regarding Massage Counter Pressure